Design Thinking Model in Clever Think Application Design - Rahma Dafitri; Iwan Sukoco (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Clever Think is one of the alternatives in the learning model. This study aims to examine the technique of designing clever think applications quickly, easily, and cheaply according to user needs.. the model can significantly reduce the weaknesses in making Clever Think applications. Design/methodology/approach: This research is a qualitative research because it describes the implementation stages of the Clever. In this research, the software that will be studied will use the System Design Model method that can engineer smartphone-based software easily and quickly Findings: The results of this study also show that this model can formulate ideas successfully and creatively to build learning applications. Research limitations/implications: This research is limited to learning applications only Practical implications: This research can be applied by lecturers, teachers as a learning solution for students during the pandemic Originality/value: This Paper is Original Paper type: Research paper